2004
DOI: 10.1161/01.cir.0000142664.18739.92
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Inflammation and Rapid Coronary Artery Disease Progression in Patients With Stable Angina Pectoris

Abstract: Background-Both endothelial cell activation and macrophage activation play a significant role in atherogenesis and atheromatous plaque vulnerability and may determine rapid coronary artery disease (CAD) progression. We sought to assess the association between serum inflammatory markers and rapid CAD progression in patients with chronic stable angina pectoris. Methods and Results-We studied 124 chronic stable angina pectoris patients (84 men; mean age, 61Ϯ10 years) who were on a waiting list for coronary angiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
151
2
15

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(186 citation statements)
references
References 48 publications
13
151
2
15
Order By: Relevance
“…Circulating levels of neopterin have been reported to be higher in patients with acute coronary syndrome (ACS) than in control subjects and in patients with stable angina pectoris (SAP) 6,7) . Furthermore, recent studies have shown a direct association between neopterin and plaque instability in coronary arteries [8][9][10][11] ( Table 1). Several coronary angiographic studies have shown a relationship between increased neopterin levels and complex coronary lesions in patients with unstable angina pectoris (UAP) 8,9) ; however, neopterin levels did not correlate with the number of diseased coronary vessels, suggesting that neopterin may be a marker of inflammatory CAD activity rather than a measure of the anatomical extent of the coronary atheromatous process 8,9) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 98%
See 2 more Smart Citations
“…Circulating levels of neopterin have been reported to be higher in patients with acute coronary syndrome (ACS) than in control subjects and in patients with stable angina pectoris (SAP) 6,7) . Furthermore, recent studies have shown a direct association between neopterin and plaque instability in coronary arteries [8][9][10][11] ( Table 1). Several coronary angiographic studies have shown a relationship between increased neopterin levels and complex coronary lesions in patients with unstable angina pectoris (UAP) 8,9) ; however, neopterin levels did not correlate with the number of diseased coronary vessels, suggesting that neopterin may be a marker of inflammatory CAD activity rather than a measure of the anatomical extent of the coronary atheromatous process 8,9) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 98%
“…Previous clinical studies have demonstrated that neopterin is associated with atherosclerotic plaque instability in coronary artery disease (CAD) [6][7][8][9][10][11][12][13][14][15][16][17] . Circulating levels of neopterin have been reported to be higher in patients with acute coronary syndrome (ACS) than in control subjects and in patients with stable angina pectoris (SAP) 6,7) .…”
Section: Neopterin and Plaque Instability In Coronary Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kararlı anjina pektorisli 297 hastanın 1 yıllık takiplerinde neopterinin majör kardiyak olayların bağımsız prediktörü olduğu gösterilmiştir (7). Artmış neopterin düzeyleri ayrıca hipertansif ve tıkayıcı olmayan koroner arter hastalıklı bireylerde istenmeyen kardiyak olay gelişimi ile (35) ve koroner revaskülarizasyon yapılan hastalarda hastalığın hızlı seyri ile ilişkili bulunmuştur (36). Serum neopterin düzeylerinin akut koroner sendromda arttığı ve çatlamış plak varlığını belirlemede, nötrofil sayısı ve CRP'den daha duyarlı olduğu gösteril-miştir (37).…”
Section: Discussionunclassified
“…Rapid CHD progression in patients with stable angina pectoris has been shown to be associated with increased C-reactive protein [CRP] levels and raised concentrations of biochemical markers of endothelial and macrophage activation [19]. Cellular adhesion molecules (CAMs) and matrix metalloproteinases (MMPs) have also been suggested to represent an important factor in atheromatous plaque disruption and the occurrence of acute coronary syndromes [20].…”
Section: Introductionmentioning
confidence: 99%